Meningkatkan Kemampuan Belajar Mengklasifikasikan Makhluk Hidup Melalui Pendekatan Team Assisted Individualy - Afriatul Hanik (Education Research Center, 2025)
This study aims to evaluate the effectiveness of the cooperative learning model with the Team Assisted Individually (TAI) approach in enhancing students' ability to classify living organisms based on their characteristics in Class VII D of SMP Negeri 2 Gresik. Conducted in two cycles, this research involved planning, implementation, observation, evaluation, and reflection stages. The findings from Cycle I indicated several challenges in implementing the TAI model, particularly concerning the teacher's readiness to manage the class and the lack of active student participation. Although most students achieved the Minimum Competency Criteria (KKM), the results did not fully meet the expected success indicators. However, improvements made in Cycle II, covering planning, execution, and evaluation, resulted in significant progress. Teachers were better prepared and more confident, students became more engaged and enthusiastic in the learning process, and student learning outcomes significantly exceeded the expected targets. By the end of Cycle II, 91.75% of students achieved learning mastery with an average score of 89.41, and students' responses to the learning process also improved to a highly positive level. These findings align with previous research, which suggests that cooperative learning, particularly using the TAI model, can enhance student engagement, social interaction, and academic performance. When implemented properly, the TAI model fosters an inclusive and collaborative learning environment, encouraging students to actively participate in learning and develop social and critical thinking skills. This study provides practical implications for teachers and educators to consider using cooperative learning models like TAI as an alternative to enhance student learning outcomes and engagement. However, the success of this learning model highly depends on the teacher's preparedness in planning, managing, and motivating students. Therefore, professional development and training for teachers are essential to improve their skills in applying cooperative learning methods. The limitation of this study lies in its limited scope, focusing on one class in a single school. Future research is recommended to expand similar studies across different schools and broader contexts to strengthen the generalizability of the findings. Additionally, further research could explore various other cooperative learning strategies to assess their effectiveness in different educational contexts. Overall, this study demonstrates that the TAI learning model is an effective approach to improving learning quality and student outcomes, and it is hoped to serve as a valuable reference for teachers, researchers, and policymakers in efforts to enhance the quality of education in Indonesia.